Understanding Transient Photoluminescence in Halide Perovskite Layer Stacks and Solar Cells. Issue 19 (9th April 2021) - Krückemeier, Lisa; Krogmeier, Benedikt; Liu, Zhifa; Rau, Uwe; Kirchartz, Thomas
Abstract: While transient photoluminescence (TPL) measurements are a very popular tool to monitor the charge‐carrier dynamics in the field of halide perovskite photovoltaics, interpretation of data obtained on multilayer samples is highly challenging due to the superposition of various effects that modulate the charge‐carrier concentration in the perovskite layer and thereby the measured photoluminescence (PL). These effects include bulk and interfacial recombination, charge transfer to electron‐ or hole transport layers, and capacitive charging or discharging. Here, numerical simulations with Sentauraus TCAD, analytical solutions, and experimental data with a dynamic range of ≈ 7 orders of magnitude on a variety of different sample geometries, from perovskite films on glass to full devices, are combined to present an improved understanding of this method. A presentation of the decay time of the TPL decay that follows from taking the derivative of the photoluminescence at every time is proposed. Plotting this decay time as a function of the time‐dependent quasi‐Fermi‐level splitting enables distinguishing between the different contributions of radiative and non‐radiative recombination as well as charge extraction and capacitive effects to the decay. Abstract : A comparison of simulations and experimental data on transient photoluminescence of halide perovskite films, stacks, and devices is presented. A representation of the decay time as a function of Fermi‐level splitting is presented that allows distinguishing the different contributions to the decay that include radiative and non‐radiative recombination as well as capacitive charging and discharging of electrodes or interfaces.